PWE-075 Endoscopic radiofrequency ablation for high-grade dysplasia or intramucosal cancer in Barrett's oesophagus – results from the first 100 patients enrolled in the UK HALO radiofrequency ablation registry. (23rd September 2015) - Dunn, J M; Thorpe, S; Fullarton, G M; Smart, H; Penman, I; Patel, P; Willert, R; Novelli, M R; Banks, M B; Lovat, L B
Abstract : Introduction: The incidences of Barrett's oesophagus (BE) and associated oesophageal adenocarcinoma are increasing rapidly in the UK. Radiofrequency ablation (RFA) with a circumferential balloon based device (CA) and endoscope-mounted focal ablation device (FA) are promising modalities for treating dysplasia arising in BE. Aim: To determine the safety and efficacy of RFA for treating dysplastic BE in a UK patient cohort. Study Design: Multicentre UK registry (seven teaching and private hospitals; treatment period from April 2007 to November 2009). Patients with histological evidence of dysplasia or intramucosal cancer (IMC) arising in BE confirmed by two specialist GI pathologists were included in the study. A prior endoscopic mucosal resection (EMR) was permitted, provided that residual dysplasia remained in the BE region for ablation. RFA was performed every 3 months with follow-up biopsy upon achieving either complete endoscopic eradication of BE or after four consecutive ablations. The primary endpoint was complete response for high-grade dysplasia (CR-HGD), dysplasia (CR-D) and intestinal metaplasia (CR-IM), defined as no biopsy showing each respective finding. Results: A total of 106 patients (79% male, median age 69 years, interquartile range (IQR) 50–83 years) have been treated so far. Accrual rates now exceed 15 patients per quarter. 83 had HGD, 22 IMC, 1 LGD. Median length of BE was 6 cm (IQR 1–15 cm). 54% had prior EMR, 25% had previous photodynamic therapy (PDT) or argon plasma coagulation (APC). 42 patients have completed treatment with at least 1 follow-up biopsy session (median follow-up 4 months, IQR 2–24). Median number of treatments is 1 CA (IQR 0–3) and 1 FA (IQR 0–3). CR-HGD was achieved in 90% of patients, CR-D in 79% and CR-IM in 33%. There were eight new strictures, three mucosal injuries during RFA (1.5%) and one perforation (patient previously treated with PDT) (0.5%). Conclusion: Reversal of IM is currently poor, but many of these patients have had multiple previous ablative therapies and may represent a particularly difficult group to treat. Despite this, radiofrequency ablation safely achieved a CR- HGD in 90% of patients treated within a UK multicentre registry. These data are similar to other registries.